Signal processing techniques of lamb waves for structural health monitoring system- A review - Nurazima, Ismail; Mohd Hafizi, Zohari; Che Eddy Nizwan, Che Ku Husin; Lim, Koksing (Semarak Ilmu Publishing, 2024)
The structural health monitoring (SHM) system using Lamb wave approach has drawn a lot of interest because of its outstanding performance in terms of accuracy and adaptability. The implemented signal processing techniques in the diagnostic analysis are specifically reviewed in this work. The primary factors of the wide range of applied signal processing techniques are due to the multimode and dispersive behaviour of the Lamb waves. Several Lamb modes occur simultaneously, and because they have different dispersive characteristics, they can produce complicated superimposed signals. To effectively diagnose the observed signals, several mode separations approaches have been proposed. Generally, time-frequency representation is applied for signal processing techniques. The findings demonstrated that the proposed procedures were successful in decomposing the superimposed mode into individual modes for further analysis. All these works have shown how SHM systems based on Lamb waves have evolved over time to control and monitor the condition of the structure.